Enhanced Production of Microbial Exocellular Biopolymers for Removal of Phosphate from Water - Kaur, Taranpreet (My University, 2015)
Phosphorus is an essential element required by all life forms for their survival and growth. Recent decades have witnessed expansion of agriculture, human population and industry resulting in increased use, and consequent elevations in discharge of phosphorus. In view of the untoward outcomes of excessive phosphorus discharge in water bodies, regulatory bodies have posed limits on phosphorus concentration in waste water. Permissible limits of phosphorus discharge are achieved through physical/chemical and biological methods of phosphate (the only bioavailable form of phosphorus) removal. However, installation and operational costs, availability of resources, phosphorus removal efficiency, recovery and reusability of phosphorus following treatment, waste management and occupational hazards are the major impediments in wide application of these methods. Sorbents derived from biological sources have gained immense interest in recent years as sustainable, non-toxic and cost effective alternatives for removal of pollutants. Despite their increasing popularity in remediation of other pollutants, biosorbents for phosphorus removal from waste water have not been extensively investigated. In fact, biosorbent-mediated phosphorus remediation has been restricted to sorbents prepared from agricultural wastes while microbial polymers have remained unexplored. The present study exploited the potential of bacterial exobiopolymer (EBP) as a biosorbent for phosphorus removal. An isolate producing phosphate-binding EBP was isolated from sludge and designated Acinetobacter haemolyticus TK15. In an attempt to potentiate EBP production, mutants were generated using Tn5 transposon mutagenesis and screened for EBP yield and phosphate removal. An insertional mutant which showed enhanced EBP production and high phosphate binding affinity was selected and designated A. haemolyticus MG606. Sequencing of Tn5 flanking regions revealed that insertion occurred in a 9 bp motif located 89 bp upstream of a bifunctional enzyme, phosphoglucomutase/ phosphomannomutase (PGM/PMM). The Tn5 insertion resulted in increased transcription of pgm gene and subsequent elevation in PGM ix activity in A. haemolyticus MG606 cell lysates. Contrastingly, enzyme activities of other enzymes involved in EBP biosynthesis (UDP-glucose epimerase, phosphoglucoisomerase and glucosyltransferase) was comparable in A. haemolyticus MG606 and A. haemolyticus TK15. The increase in PGM activity was accompanied by an increase in a downstream metabolite, UDPglucose, which also serves as a precursor in EBP biosynthesis. Purified PGM/PMM exhibited optimal activity at 35°C and pH 7.5. EBP produced by A. haemolyticus MG606 was characterized by physical, chemical and spectroscopic methods to understand its composition and physicochemical properties. Scanning electron microscopy and X-ray diffraction analysis revealed porous and amorphous nature of EBP while nitrogen sorption studies revealed surface area of 87.8 cm2/g. The biopolymer was found to be polysaccharide in nature consisting of 48.9 KDa heteropolysaccharide composed of galactose, glucose, xylose, lyxose, allose, ribose, arabinose, mannose and fructose units. The exobiopolymer was found to be thermal stable with degradation temperature of 290°C. Aqueous solution of EBP exhibited viscoelastic properties characteristic of shear-thinning, non- Newtonian, pseudoplastic liquids. Toxicity studies revealed LD50 of 12.11 log CFU/mouse for A. haemolyticus MG606 and 92.31 mg/kg for EBP following intraperitoneal administration in Swiss albino mice. No apparent toxicity was observed in cell lines (RAW 264.7 and A549) for up to 400 μg/mL EBP. To elucidate the nature of phosphate binding with EBP, phosphate binding was determined as a function of contact time, EBP concentration and phosphate concentration. Phosphate binding was maximal at 100 mg/L EBP and 240 min contact time. Phosphate sorption on EBP was modeled by various isotherm equations and was best described by Langmuir isotherm with maximum phosphate binding capacity of 25 mg/g of EBP. In order to further characterize the nature of phosphate-EBP interactions, the mechanism of phosphate binding was determined by x physicochemical and spectroscopic methods. Phosphate binding was attributed to polysaccharides and protein fractions of biopolymer and involved ligand exchange mechanism via hydroxyl groups and electrostatic interactions via amino groups. The culture conditions were optimized to enhance EBP production by A. haemolyticus MG606. The pH, temperature, carbon and nitrogen sources were optimized in shake flask using one factor at a time method and optimal conditions were found to be temperature 35°C, pH 6.5, inoculum size 1%, agitation speed 120 rpm, glucose and acetate as carbon source and ammonium sulphate as nitrogen source. The concentrations of carbon and nitrogen sources were further optimized in a 5 L bioreactor using central composite design of response surface methodology. The highest EBP yield was observed at 5.454 g/L glucose, 4.506 g/L sodium acetate and 0.358 g/L ammonium sulphate. The growth kinetics and EBP production under optimized conditions was modeled using Leudeking-Piret model and EBP production was found to be partially growth associated. To determine the applicability of EBP in phosphate detection, an optoelectronic biosensor was fabricated. The biosensor response was linear in the concentration range 1-10 mg/L phosphate. The limit of detection and limit of quantification of biosensor were 0.5 and 1 mg/L of phosphate, respectively. The applicability of EBP in remediation of water was determined in column studies using EBP-containing calcium alginate hydrogel beads. Phosphate removal by hydrogel beads followed Thomas model. Overall, the results of the present study suggest EBP produced by A. haemolyticus MG606 has potential applications in phosphate sensing and remediation.
Ph.D. (Biotechnology)
Keywords: Acinetobacter haemolyticus; phosphate binding exobiopolymer; biosensor; sorption isotherms; phosphoglucomutase; Biotechnology